Resection and anastomosis of the supracarinal trachea by post-inflammatory stenosis - Bergalli, Luis E.; Mesa, Guillermo; Fossemale, Estela; Ayala, Walter; Suárez, Raúl; Pradines, Jorge (Cirugía del Uruguay, 1979)
The paper describes a case of supracarinal post-tracheostomy tracheal stenosis, 10 months after intubation and prolonged assisted ventilation. The most important paraclinical elements are discussed. In view of the fact that coordinated management hetween anesthesiologists and surgeons is the most important part from the point of view of tactics, the authors stress those manouvres which are essential in successful therapy.